2)
Пусть
![image](https://tex.z-dn.net/?f=+x%5E%7B3%7D+%3Da+%3D%3E+x%5E%7B6%7D%3D+a%5E%7B2%7D++%3D%3E+a%5E%7B2%7D%2B8%3D9a+%3D%3E+a%5E%7B2%7D-9a%2B8%3D0+%3D%3E)
x^{6}= a^{2} => a^{2}+8=9a => a^{2}-9a+8=0 =>" alt=" x^{3} =a => x^{6}= a^{2} => a^{2}+8=9a => a^{2}-9a+8=0 =>" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+a_%7B1%7D+%3D8%3B+a_%7B2%7D+%3D1+%3D%3E++x%5E%7B3%7D+_%7B1%7D%3D8%3D%3E+x+_%7B1%7D%3D2%3B+x%5E%7B3%7D+_%7B2%7D%3D1+%3D%3E+x+_%7B2%7D%3D1)
x^{3} _{1}=8=> x _{1}=2; x^{3} _{2}=1 => x _{2}=1" alt=" a_{1} =8; a_{2} =1 => x^{3} _{1}=8=> x _{1}=2; x^{3} _{2}=1 => x _{2}=1" align="absmiddle" class="latex-formula">
Ответ: (2;1), (1;2)